Process development of health benefits from corn in pet diets that enhance dog utilization - Lierz, Ryan William (Kansas State University, 2022)
The methods of manufacturing pet diets have evolved over the past 160 years. Starting with a baked biscuit in 1860 to the widely used extrusion technology today. Formulas have also changed with once popular corn now being criticized as inferior and indigestible. Different processing methods can change starch digestion. Less processing can lead to more indigestible starch (resistant starch; RS) within corn diets. This RS may benefit gastrointestinal health. Therefore, the objective of the first study was to determine the effect of process on dietary utilization of corn-based diets, and changes to starch utilization. Experimental diets containing 56% corn as the sole starch source were produced through pelleting, baking, and extrusion and compared to a baked control diet in which the corn was replaced with dextrose. The pelleted diet had the highest (P < 0.05) differential scanning calorimetry (DSC) residual gelatinization peak (3.5 J/g) followed by the baked diet (1.4 J/g), and then similar to the extruded diet the control had the lowest result (0.1 J/g). The extruded diet resulted in the highest (P < 0.05) level of gelatinized starch (34.2%) by the glucoamylase procedure followed by the baked treatment (14.7%) and pelleted had the lowest (P < 0.05) gelatinized starch (8.4%). As a percentage of total starch, the extruded diet had the highest (P < 0.05) level of rapidly digestible starch (90.0%), the baked treatment was intermediate (P < 0.05, 60.9%) and pelleted the lowest (P < 0.05, 34.8%). The pelleted diet had the highest (P < 0.05) amount of slowly digestible starch (SDS, 42.6%), with the baked treatment having an intermediate (P < 0.05) amount of SDS (27.1%), and the extruded diet had the lowest (P < 0.05) amount of SDS (7.1%) Among corn treatments the extruded diet had the lowest (P < 0.05) level of RS (1.3%). The baked diet was intermediate (P < 0.05, 3.6%) with the highest RS (P < 0.05) in the pelleted diet. To evaluate the in vivo effects of these process treatments, twelve Beagle dogs were fed the experimental diets for 9 d adaptation and 5 d of collection in a replicated 4 x 4 Latin square designed study. The data were analyzed using the general linear mixed model with statistical analysis software (GLIMMIX proc; SAS v9.4, Cary NC) and means were considered different at ∝=5%. The experimental diet was the fixed effect with period and dog as random effects. Dogs were fed to maintain body weight, with food intake similar among corn treatments and lower (P < 0.05) for those fed the control diet. Fecal scores (1: soft-liquid to 5: hard-dry) were slightly different across the three corn treatments, but each exceeded 3.5 which was considered ideal. However, dogs fed the control diet (dextrose) had soft-runny stools (average score of 1). Feces from dogs fed the baked treatment had a lower fecal pH (5.37; P < 0.05) than the other corn treatments (average 5.71); whereas the pH of feces from the dogs fed the control (dextrose) diet were the highest (P < 0.05) at 6.87. The dry matter apparent total tract digestibility (ATTD) was greater (P < 0.05) for the dogs fed the extruded corn-based diet and the control diet (average 75.75%) versus the baked and pelleted diets (average 69.49%). In conclusion, the corn diets had different levels of gelatinized starch thereby influencing the in vivo digestibility, Resistant starch was higher in treatments of lower cooking intensity including lower fecal pH which may indicate improved colonic fermentation leading to positive impacts on gut health. To assess the level of RS in commercial products for comparison purposes, 30 baked dog treats were evaluated in a 2 x 3 factorial design. Samples were purchased and separated into main effects of size (small, medium, large), and presence or absence of wheat. Samples were analyzed for their resistant starch concentration. It was determined that the size and presence of wheat did not impact the total starch (average 40.7%), digestible starch (average 39.5%), or resistant starch (average 1.8%) concentration. However, a post-hoc analysis did indicate the few (n=5) grain-free products that were selected had a higher (P < 0.05) concentration of resistant starch (average 4.9%). In conclusion, among treatments like extrusion that had more energy inputs there was a lower concentration of RS while the inverse was observed in processes with fewer energy inputs or lower cooking intensity. This also impacted stool quality and the digestion of some nutrients but significantly increased starch digestion. Treatments with lower levels of RS are common to commercially available foods. So, using different processing methods can change the digestible and indigestible starch ratio, which can have promote several health benefits.
Keywords: Resistant starch; Dog; Baked; Digestibility